KERENTANAN KEBAKARAN HUTAN BERDASARKAN KARAKTER UMUR TANAMAN JATI - Ardiansyah, Fiqri; Triyogo, Ananto (Fakultas Kehutanan Universitas Lancang Kuning, 2021)
Forest management in Java dominated with Teak plantation that organize with community. One threats of forest damages is forest fires. Forest fires caused by susceptible fuel, oxygen rate, and fires resource. Teak plantation closed with community activities that using fires within purpose or not. This research aim to identify the effect of plant age towards forest fires susceptibility by combustion rate. This research conducted in Wanagama I EduForest. The effects of plant age towards forest fires susceptibility analysed by bark thickness and water content of bark. Teak bark samples taken on various age of 5th, 15th, and 40th. Foresf fires suceptibility observed by combustion test. The effects of teak age towards on bark thickness and water content, combustion rate analysed using anova with 10% of confident level. The results showed that 1) plant age affecting thickness and water content of teak bark; 2) bark thickness affect fire susceptibility rate of teak on various age, bark thickness has growth along age increase which more tolerant towards of combustion; and 3) Surface forest fires in Wanagama I caused by multiple sources of fire ignition that closed to road accesibility, and the damage mostly occurred until 100 cm of height from forest ground.